Prevalence of Renal Artery Stenosis in Patients Undergoing Routine Coronary Angiography - Sakib, Md Annaz Mus; Talukder, Ranjan; Morshed, Maruf; Islam, Md Saiful (KYAMC Journal, 2013)
This retrospective observational study aimed to see the angiographic association of at Renal-Artery Stenosis (RAS) with Coronary Artery Disease(CAD) in Bangladeshi population. It was conducted in the department of cardiology, Khwaja Yunus Ali Medical College and Hospital (KYAMCH), Enayetpur, Sirajgonj, Bangladesh, from January 2007 to January 2009.A total 281 patients with Ischaemic heart disease, on non emergent coronary angiogram who underwent either selective or non selective renal angiography were enrolled in this study. Among 281 patients, male patients was 241(85.76%), female was 40(14.23%) and age group was 30-75 years. Among those patients 228(81%) patients had Coronary artery disease, 53(18.86%) patients had normal coronary artery. Among CAD, 51(18.14%) patients had single vessel disease (SVD),39(13.87%) patients had double vessel disease (DVD),124(44.12%) patients had triple vessel disease(TVD) and 14(4.9%) patients had minimal coronary artery disease. RAS was detected 23(8.18%) patients and RAS with HTN was 18(78%) patients and ARAS without HTN was 5(21.73%) patients. RAS tends to increase with age. In age group 30-45 years, RAS was 17.39% and age group 50-75 it was 82.60%.The incidence of was high in50.09±8.76 years. Incidence of RAS was more common in male patients (73.91% vs. 26.08%). DOI: http://dx.doi.org/10.3329/kyamcj.v2i1.13513 KYAMC Journal Vol.2(1) 2011 pp.109-113